ANALISIS KOMPETENSI GURU PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SEKOLAH DASAR INKLUSIF - Abdul Rahim; Endang Hangestiningsih; Taryatman Taryatman (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to describe and find the needs of physical education teachers in inclusive primary schools in the city of Yogyakarta. The scope of this research is the competency of physical educationÂ teachers in terms of; 1) pedagogik competence, 2) professional competence, 3) personality competence, 4) sosial competence. The results showed that 1) the pedagogik competence of teachers in SD A, B, and C was very good, 2) Professional teacher competencies were still lacking especially in planning and assessment of learning outcomes in inclusive classes, 3) The personality competencies of the teachers showed good results, 4) The sosial competencies of the teachers in SD, A, B and C also show very good. This means that the basic needs of Â physical educationÂ teachers are professional competence.